Clinical evolution of sacral stress fractures: influence of additional pelvic fractures. Issue 7 (July 1993) - Peris, P; Guañabens, N; Pons, F; Herranz, R; Monegal, A; Surís, X; Muñoz-Gómez, J
Abstract : OBJECTIVES--To evaluate the clinical evolution of sacral stress fractures in relation to the scintigraphic pattern and the presence of additional pelvic fractures. METHODS--This was a retrospective study of 14 patients with sacral fractures. RESULTS--Six patients had additional pelvic fractures. Four bone scintigraphic patterns were found. The resolution of symptoms was longer in patients with associated pelvic fractures (30 weeks v three weeks). No relation was found between the bone scintigraphic pattern and the time of evolution. CONCLUSION--Associated pelvic fractures delay the resolution of symptoms in patients with sacral fractures, regardless of scintigraphic pattern.